(untitled) (International Journal of Food and Nutritional Sciences, 2022)
act Quantitative analysis of the basin geometry has been attempted for the Vel River Basin, sub-basin of Bhima River basin. The quantitative parameters worked out include the linear, areal and relief aspects. The significance of this study is to understand the drainage network relationship and to suggest the means of better utilization of water resources in the basin